Journal of Instrumentation - Naumenko, G. A. physicist senior research fellow, Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences 1947- (2018)
As is generally known, the integral of the electric field strength over all time for usual (bipolar) radiation is zero. The first demonstration of the possibility of unipolar radiation generation has been considered theoretically by Bessonov in 1981 [E.G. Bessonov, Zh. Eksp. Teor. Fiz. 80 (1981) 852]. According to this work, the unipolar radiation (or strange electromagnetic waves) is radiation for which the integral of the electric field strength over the entire duration of a pulse differs significantly from zero. Later, several theoretical papers devoted to this phenomenon have appeared in the literature, where authors investigated mainly synchrotron radiation. However, despite the critical interest, the experimental investigations ignored this effect. In this paper we present results of the first experimental investigation of the unipolar radiation generated by a relativistic electron beam. To detect the unipolar radiation the detector that is sensitive to the selected direction of the electric field strength has been elaborated and tested. We used a designed detector to observe the coherent backward diffraction radiation appearing when a bunched electron beam travels in the vicinity of a flat conductive target. The asymmetry of the electric field strength of the coherent backward diffraction radiation has been demonstrated.